Uso do ringer lactato na correção da depleção de cetoacidose diabética - Fernanda Lorena de Souza; Adriana Koliski; Wendell Paiva Vita; Marcelo Rodrigues; Heloísa Luis Marques (Residência Pediátrica)
INTRODUCTION: Diabetic ketoacidosis (DKA) is an emergency often associated with dehydration, and volume replacement is one of its therapeutic pillars. The best fluid for this is uncertain. This study aims to compare the use of Ringer lactate (RL) and saline0.9% (SF0.9%) in the correction of DKA depletion in pediatrics patients. METHODOLOGY: Cross-sectional and analytical study, with ambispective data collection. The inclusion criteria were patients aged 0-14 years, diagnosed with DKA, who received a correction for depletion with SF0, 9% or RL, in the first 24 hours of treatment. The primary outcome was the resolution time of DKA. Secondary outcomes were the amount of insulin infused, volume received and changes in serum sodium, chloride, anion gap, blood glucose, and lactate levels over 24 hours. RESULTS: 48 hospitalizations were included: 33 received 0.9% SF and 15 received RL. The median age was 123.5 (20.9-167.2) months and 54.2% were female. The duration of DKA was observed to be lower in the RL group (median: 18 [4-39] hours) compared to the SF0.9% group (median: 24 [6-80] hours) (p=0.018). Regarding the rate of insulin infusion, a greater percentage change per hour was shown in the SF0,9% group than in the RL group (p<0,001). Regarding laboratory measurements, there was no statiscal difference between variables in the subgroups. CONCLUSIONS: The use of TL was associated with faster resolution of DKA compared to that of saline. It suggests that balanced crystalloids may be preferred in the treatment of DKA depletion corretion in pediatric patients.